Alternatif Pembiayaan Untuk Pengadaan Kendaraan Operasional Antara Lesing Dan Kredit Bank - Negara, I Kadek Putra (E-Jurnal Manajemen, 2012)
This study aims to identify and provide an overview in selecting a more favorable financing alternative between leasing and bank loans. In this study using the present value cash out flow and analysis of good and evil. The result showed that for vehicle finance operation, a favorable alternative is the present value of bank credit due to bank loans is lower than the lease, where the lease alternative present value that was obtained for Rp. 94.863.900,- while the present value of bank loans obtained Rp. 78.232.210,- . Some of the advantages of bank credit shoes as a lower installment payment, the absence of additional collateral and bank credit into an alternative financing on large scale. So by using a bank loan financing would be more profitable.
Keywords: alternative financing, leasing, bank credit